PENGARUH KUALITAS PELAYANAN RELIABILITY, RESPONSIVENESS DAN ASSURANCE TERHADAP KEPUASAN PASIEN RUMAH SAKIT MUHAMMADIYAH (MOTIVASI, 2023)
Purpose– This study aims to determine the effect of Reliability, Responsiveness and Assurance simultaneously and partially on Patient Satisfaction at Muhammadiyah Hospital Palembang.  Design/methodology– This study used 100 samples, the sampling technique used a non-probability sampling technique by means of purposive sampling. The type of research used is associative, the data used are primary data and secondary data. Data collection techniques used are questionnaires and documentation. The analysis technique used is Multiple Linear Regression analysis, F test, t test and the coefficient of determination. The results of the Multiple Linear Regression analysis of the Reliability, Responsiveness and Assurance variables have a positive regression coefficient meaning that Reliability, Responsiveness and Assurance have a positive influence on changes in patient satisfaction Findings - The results of the F test analysis conducted showed that there was a significant effect of Reliability, Responsiveness and Assurance on Patient Satisfaction at Muhammadiyah Hospital Palembang. The results of the partial t hypothesis test show that Reliability, Responsiveness or Assurance have a significant effect on Patient Satisfaction. The coefficient of determination analysis showed that 83.8% of changes in patient satisfaction were caused by the large contribution of the independent variables to the dependent variable in the study, while the remaining 16.2% was caused by other variables not included in this study..